Camptothecin encapsulated in β-Cyclodextrin-EDTA-Fe3O4 nanoparticles induce metabolic reprogramming repair in HT29 cancer cells through epigenetic modulation: a bioinformatics approach - Farhana, Aisha; Ee, Avin Hwan Koh; Mok, Pooi Ling; Alsrhani, Abdullah; Khan, Yusuf Saleem; Subbiah, Suresh Kumar (Multidisciplinary Digital Publishing Institute, 2021)
Cancer progresses through a distinctive reprogramming of metabolic pathways directed by genetic and epigenetic modifications. The hardwired changes induced by genetic mutations are resilient, while epigenetic modifications are softwired and more vulnerable to therapeutic intervention. Colon cancer is no different. This gives us the need to explore the mechanism as an attractive therapeutic target to combat colon cancer cells. We have previously established the enhanced therapeutic efficacy of a newly formulated camptothecin encapsulated in β-cyclodextrin-EDTA-Fe3O4 nanoparticles (CPT-CEF) in colon cancer cells. We furthered this study by carrying out RNA sequencing (RNA-seq) to underscore specific regulatory signatures in the CPT-CEF treated versus untreated HT29 cells. In the study, we identified 95 upregulated and 146 downregulated genes spanning cellular components and molecular and metabolic functions. We carried out extensive bioinformatics analysis to harness genes potentially involved in epigenetic modulation as either the cause or effect of metabolic rewiring exerted by CPT-CEF. Significant downregulation of 13 genes involved in the epigenetic modulation and 40 genes from core metabolism was identified. Three genes, namely, DNMT-1, POLE3, and PKM-2, were identified as the regulatory overlap between epigenetic drivers and metabolic reprogramming in HT29 cells. Based on our results, we propose a possible mechanism that intercepts the two functional axes, namely epigenetic control, and metabolic modulation via CPT-CEF in colon cancer cells, which could skew cancer-induced metabolic deregulation towards metabolic repair. Thus, the study provides avenues for further validation of transcriptomic changes affected by these deregulated genes at epigenetic level, and ultimately may be harnessed as targets for regenerating normal metabolism in colon cancer with better treatment potential, thereby providing new avenues for colon cancer therapy.